Information technology: a tool for effective SME material management practices - Ibrahim, Magaji Umar; Kasim, Narimah; Gidado, Umar (International Journal of Innovative Research and Development., 2019)
Nowadays, various strategies have been adopted to ensure reduction or elimination of waste in materials management practices in the construction industry for overall project performance. However, there are significant challenges related to Small and Medium Enterprises (SME) materials management practices, these challenges arise due to shortage of skills, practical know how, workers capability and financial difficulties in information technology (IT) adoption. Therefore, the aim of this study is to explore the potentials of IT as a tool for waste elimination or reduction in the Nigerian SME materials management practices for overall projects performance. The data were collected using structured questionnaires and administered to SME in the construction industry in the Northeast of Nigeria. The obtained data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to determine significant level of IT in SME materials management practices. Outcome from the model of this study revealed that, IT adoption is significant with R2 =0.622 (62.2%) which indicates that adoption of IT can improve SME materials management practices for overall projects performance.